The Association of Acute Kidney Injury and Atrial Fibrillation after Cardiac Surgery in an Asian Prospective Cohort Study. Issue 12 (March 2016) - Ng, Roderica Rui Ge; Tan, Gabriel Hong Jie; Liu, Weiling; Ti, Lian Kah; Chew, Sophia Tsong Huey
Abstract : Abstract: Acute kidney injury (AKI) and atrial fibrillation (AF) after cardiac surgery are common occurrences and increase patient morbidity and mortality. Inflammation plays a role in increased incidence of AF in patients with chronic kidney disease (CKD); reactive oxygen species and inflammatory markers which are increased in patients with CKD were found to affect the proper functioning of the intracellular ion channels, connexions (transmembrane proteins found in intercellular gap junctions), and electrical homogeneity of the extracellular matrix which are essential for electrical stability and proper conduction of electrical impulses in the atrium. However, it is not known if similar mechanisms are also involved in AKI. We tested the hypothesis that patients with AKI after cardiac surgery have a higher incidence of postoperative AF. Data from 2885 patients, who had undergone cardiac surgery between August 2008 and July 2012 from the Singapore's 2 major heart centers, were obtained prospectively. Postoperative AKI was defined using the Acute Kidney Injury Network criteria. The primary outcome was postoperative AF, and subjects were considered to have postoperative AF if the AF lasted more than an hour, affected hemodynamics, or required medical treatment. The incidence of AKI was 29.7% and the incidence of postoperative AF was 16.8%. A total of 27.7% of AKI patients developed AF. Patients with AKI had a 2-fold increased risk of developing AF (relative risk [RR], 1.716; 95% confidence interval [CI], 1.433–2.055; P  < 0.001). The following factors were found to independently increase the risk of AF in patients with AKI: age (RR, 1.011; 95% CI, 1.000–1.022; P  = 0.04), low preoperative hemoglobin (RR, 0.942; 95% CI, 0.888–1.000; P   =  0.05), low preoperative estimated glomerular filtration rate (eGFR) (RR, 0.987; 95% CI, 0.980–0.994; P  < 0.001), and lowest hematocrit during bypass (RR, 0.943; 95% CI, 0.910–0.978; P  < 0.001). Patients with AKI are more likely to develop postoperative AF. These patients were older and had lower preoperative hemoglobin, eGFR, and lower nadir hematocrit during bypass. Identification of high-risk AKI patients with early prevention and treatment of AF should reduce the long-term morbidity and mortality among Asian patients undergoing cardiac surgery.